Leadership Style in Transforming the Business Landscape - Amran, Noor Afza; Saad, Natrah; Abdullah, Zarifah; Ibrahim, Marhaiza (Panoply Consultancy, 2017)
This study focuses on the attributes of prominent Malaysian woman leader. Specifically,this study attempts to understand how a woman business leader from the healthcare industry has succeeded in her career, the attributes that have contributed to her success, and her leadership style. An interview with the woman business leader was conducted to gather the information.Results reveal that the attributes portrays by participant is consistent with top qualities of great leaders, include being visionary, being meticulous, being determined, having integrity, being passionate and being an eloquent speaker. In addition, a participative leadership style has proven to be able to transform the private healthcare landscape in Malaysia. The findings would add to the existing literature on leadership attributes and styles of women business leaders, particularly in the ASEAN region. Practically, the findings would be of importance to young entrepreneurs who aspire to be industry leaders.